Pengaruh Pendidikan Kesehatan tentang Personal Hygiene saat Menstruasi Melalui Media Video Terhadap Pengetahuan dan Sikap pada Siswi SMP Negeri 29 Samarinda - Mey Reta Chandra; Sri Hazanah; Dian Ardyanti (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2023)
Abstract Background: Maintaining personal cleanliness and health is something that people do on a regular basis to prevent reproductive diseases. According to a number of research, teens are less knowledgeable about personal hygiene. This study aims to assess the efficacy of a video-based education program on the knowledge and attitudes of female students at SMP Negeri 29 Samarinda on menstrual hygiene. Objective: The purpose of this study was to evaluate the knowledge and attitudes of female students at SMP Negeri 29 Samarinda on the impact of health education on menstrual hygiene through video media. Research methods: This team's setup for pre and post-testing. A pair of measurements, taken before and after the intervention, make up this method. By comparing findings from before and after the intervention on the posttest, we can be sure that the results from the intervention are reliable. Results: When comparing students' understanding before and after the intervention, we find that 15 students (18.1%) have a very good grasp of the material. Not only that, but it is common knowledge that the vast majority of knowledgeable respondents have p-values of 0.000 (p 0.05). Analysis of student attitudes before and after the intervention revealed that zero students (0.0%) rated their experience as "very good" before the intervention, while as many as forty-two students (50.6%) rated their experience as "very good" afterward. Health education by video on knowledge is effective in improving menstrual hygiene with a p-value of 0.000 (p <0.05). Conclusion:, health education regarding menstrual hygiene through video media has an impact on students at SMP Negeri 29 Samarinda in terms of knowledge and attitudes. Adolescent female pupils are likely to benefit from this study's input and knowledge. Keywords: Information, Attitude, and Personal Hygiene.